Diversidad de escarabajos copronecrófagos (Coleoptera: Scarabaeidae) en tres estados de sucesión del bosque de la Reserva Tapichalaca del Cantón Palanda - Paladines Hurtado, Fausto Alejandro (2022)
Anthropogenic activities such as cattle and agriculture have modified ecosystems, which private efforts have attempted to restore and are in different stages of succession. Bioindicator species such as copronecrophagous beetles can be used to evaluate the conservation status of these areas. In this study we estimated the diversity of dung beetles (Coleoptera: Scarabaeinae) in three stages of forest succession, natural forest, restored forest (22 years of conservation), and pasture (14 years of conservation) of the Tapichalaca Reserve in the canton of Palanda in the Province of Zamora Chinchipe. Three 250 m linear transects were used, and 162 pitfall traps were placed with baits interspersed with human excrement and chicken viscera. Three repetitions were carried out in November, December and January. A total of 465 specimens were collected, where six genera and 10 species were recorded. The natural forest and the restored forest presented average diversity and uniformity and are comparable to each other; the pasture presented lower diversity and uniformity. In terms of richness and abundance, the natural forest had the highest number of species (8) and 161 individuals, the restored forest had seven species, but a higher abundance of individuals (n=217), and the pasture had three species and 85 individuals. The analysis by the IndVal method determined that the indicator species for the natural forest and restored forest was Eurysternus caribaeus. The diversity of dung beetles in the Tapichalaca reserve is at a medium level; the age of recovery of each successional stage may influence the richness and abundance of these beetles. Key words: Dung beetles, bioindicators, restoration, conservation gradient.